2021
DOI: 10.3390/molecules26092527
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of β-1,4-Endoxylanase Production by an Aspergillus niger Strain Growing on Wheat Straw and Application in Xylooligosaccharides Production

Abstract: Plant biomass constitutes the main source of renewable carbon on the planet. Its valorization has traditionally been focused on the use of cellulose, although hemicellulose is the second most abundant group of polysaccharides on Earth. The main enzymes involved in plant biomass degradation are glycosyl hydrolases, and filamentous fungi are good producers of these enzymes. In this study, a new strain of Aspergillus niger was used for hemicellulase production under solid-state fermentation using wheat straw as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…was 55 °C [ 63 , 64 , 65 , 66 , 67 ]. Lower and higher temperatures reduce the specific activities for the reason that the thermal effects of such temperatures on both the growth of microorganisms and the rate of enzymatic reaction inside the cells imitate the vital construction of the enzyme [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…was 55 °C [ 63 , 64 , 65 , 66 , 67 ]. Lower and higher temperatures reduce the specific activities for the reason that the thermal effects of such temperatures on both the growth of microorganisms and the rate of enzymatic reaction inside the cells imitate the vital construction of the enzyme [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…RSM optimization of xylanase yield by Aspergillus niger 3-fold and 1.41-fold purification was attained with about 6.2% yield, and the highest activity of the purified xylanase was observed at pH 6 and 50°C. The produced xylanase exhibited high thermal and pH stability, with more than 90% residual activity between 30 and 40°C and pH 3-9 after incubation of 24 h, with half-lives of 30 min at 50 and 60°C [ 43 ]. Liet al [ 36 ] reported a temperature range of 50-60°C suitable for the industrial application of xylanase from P. oxalicum ZH-30.…”
Section: Discussionmentioning
confidence: 99%
“…The free inoculum of the yeasts ( P. pastoris and P. kudriavzevii ) was cultured in YPD (yeast extract, peptone and dextrose) media for 24 to 48 h, and the cells were counted manually using a Neubauer chamber under a light microscope [ 62 ]. Further, 1 × 10 5 yeast cells/mL were added to fermentation media containing 1% cress seed mucilage polysaccharides as a carbon source and 1 g/L, ammonium chloride (NH 4 Cl) as a nitrogen source.…”
Section: Methodsmentioning
confidence: 99%